(untitled) (Global Journal of Science Frontier Research, 2021)
Soil contamination with heavy metals occurs as a result of both anthropogenic and natural activities. This research was designed to investigate the effect of different application rates of Lead (Pb) on urease, phosphates and microbial community structure. The study was a screen house experiment, and was carried out in the Department of Soil Science, University of Uyo, between March to October 2018. The experiment was a pot experiment, and Lead nitrate (Pb(NO 3 ) 2 ) solution was added to wet soil sample at the rates of 0, 150, 300, and 500mg/500g soil and mixed thoroughly and incubated for 12 weeks. Samples were collected at two weeks (2wks), nine weeks (9wks), twelve weeks (12wks) after incubation for analysis of urease, acid and alkaline phosphates, and microbial populations. The results revealed that urease (URE), Acid Phosphatase (ACP), and alkaline phosphatase (ALP) were significantly lower in Pb amended soil samples than those of the control. The urease inhibition rate increased with increasing Pb concentrations. The result was more significant at two weeks of incubation,(28.33%) of the control.